Hydraulicing operation at a mining claim, probably vicinity of Nome, Seward Peninsula, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Hot Air Bench" Original image in Hegg Album 28, page 11. Original photograph by Eric A. Hegg 1773; copied by Webster and Stevens 88.A Nome Gold Rush.